light on the Diwan of Construction in India in the Mamluk and Khalji era (602-720A.H. / 1206-1321A.D.) - Khalil, Liqa (Journal of College of Education, 2022)
Abstract : The research aims to shed light on the Diwan of Construction in India in the Mamluk and Khalji era (602-720 AH/ 1206-1321AD),It is considered one of the important bureaus for any state or emirate because of its important and active role in arranging political and administrative matters in the state, if it constitutes a manifestation of stability in the state, and its importance in the development of written methods and the renaissance of the prose texts that writers wrote at the time, and as the Diwan of Inshaa represented a literary school. Anyone who finds in himself the desire and ability to learn to write qualifies for it. The research relied on a number of sources and references related to the history of Islamic India.